2018
DOI: 10.3171/2017.7.jns17668
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-mediated oncogenicity in vitro and in an animal model of glioblastoma

Abstract: OBJECTIVE Dexamethasone, a known regulator of mesenchymal programming in glioblastoma (GBM), is routinely used to manage edema in GBM patients. Dexamethasone also activates the expression of genes, such as CEBPB, in GBM stem cells (GSCs). However, the drug's impact on invasion, proliferation, and angiogenesis in GBM remains unclear. To determine whether dexamethasone induces invasion, proliferation, and angiogenesis in GBM, the authors investigated the drug's impact in vitro, in vivo, and in clinical informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…DEX significantly increased the invasive properties of the GSC3 cell line, both in vitro and in vivo . Moreover, using both GSC3 and GSC6 lines, the drug promoted proliferation and angiogenesis, in vivo (Luedi et al, 2018). The results of this interesting study, have questioned the use of DEX in GBM therapy, highlighting its ability to increase the aggressiveness of the tumor.…”
Section: Dex Therapy In Gbmmentioning
confidence: 99%
“…DEX significantly increased the invasive properties of the GSC3 cell line, both in vitro and in vivo . Moreover, using both GSC3 and GSC6 lines, the drug promoted proliferation and angiogenesis, in vivo (Luedi et al, 2018). The results of this interesting study, have questioned the use of DEX in GBM therapy, highlighting its ability to increase the aggressiveness of the tumor.…”
Section: Dex Therapy In Gbmmentioning
confidence: 99%
“…In a retrospective clinical study, the administration of dexamethasone during concomitant chemoradiotherapy with temozolomide resulted in poor prognosis in newly diagnosed GBM patients 30) . Recently, Luedi et al 20) observed the effect of dexamethasone in patient-derived GBM stem cells. They found that when exposure to dexamethasone, isocitrate dehydrogenase 1 (IDH1) wild-type cells (typical of primary GBM) showed significantly higher invasion, cell proliferation, and angiogenesis than IDH1 mutant-type GBM stem cells.…”
Section: Dexamethasone Reduces Cell Death Of Malignant Glioma Cells Amentioning
confidence: 99%
“…In this study, we analyzed the angiogenic potential of nanoceria in long-range nerve defect in vivo for the first time. We included CD31 and CD34, two markers for angiogenesis (Luedi et al., 2018, Wang et al., 2017). The neovascularization was assessed upon several indicators, including microvessel density (MVD), vessel-like structure (VLS) area, and density ((VLS area+ CD31/CD34+ area)/total scaffold area) at 6, 12, and 18 weeks after surgery.…”
Section: Resultsmentioning
confidence: 99%